Labor force participation of Mexican elderly: The importance of health - Van Gameren, Edwin (Estudios Económicos de El Colegio de México, 2008)
The determinants of the labor force participation of people in Mexico aged 50 and over are analyzed using data of the Mexican Health and Aging Study (MHAS). In particular we study the importance of health in the participation decision, taking into account the potential endogeneity of health. The results indicate that a better health causes a stronger attachment to the labor market. We find no clear evidence that employment affects health, but it cannot be ruled out that the effects of bad labor circumstances and justification eliminate each other. There are indications that self-assessed health does not capture all relevant aspects of health. For policy decisions the direct importance of financial circumstances could be more relevant than the role of health.